Pedagogical Strategies for Developing Students’ Creative and Professional Skills in Visual Arts Education - Eshmatov Samariddin Hamza oʻgʻli (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article investigates pedagogical strategies for enhancing students’ creative and professional skills in visual arts education. It analyzes interactive teaching methods, project-based learning, individual and group work, and motivational techniques as tools for fostering students’ artistic abilities. The study highlights the importance of creating a supportive classroom environment and adapting teaching approaches to students’ personal characteristics to optimize creative and professional development.